2019
DOI: 10.1089/pop.2018.0025
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic and Socioeconomic Disparities in Total Knee Arthroplasty 30- and 90-Day Readmissions: A Multi-Payer and Multistate Analysis, 2007–2014

Abstract: Previous studies have addressed racial/ethnic and socioeconomic disparities in total knee arthroplasty (TKA) within the Medicare population. However, there is limited research examining these disparities across racial/ethnic and socioeconomic groups in the general population. This study used administrative data from the State Inpatient Databases from the Healthcare Cost and Utilization Project for the years 2007-2014 from California (2007-2011 only), Florida, New York, and Maryland (2012-2014 only). In all, 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…Consistent with a growing body of literature showing that black race is a risk factor for poor outcomes after TJR [27][28][29][30][31][32], black race was a significant independent predictor of risk of complications after TJR in the present study. Potential modifiers of racial disparities in TJR outcomes include socioeconomic status and access to health care [28,31].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with a growing body of literature showing that black race is a risk factor for poor outcomes after TJR [27][28][29][30][31][32], black race was a significant independent predictor of risk of complications after TJR in the present study. Potential modifiers of racial disparities in TJR outcomes include socioeconomic status and access to health care [28,31].…”
Section: Discussionsupporting
confidence: 90%
“…17 Multiple studies have attempted to address these disparities and have analyzed universally insured databases, private payer systems, and conducted a multistate analysis to observe trends in TJA by race and other socioeconomic factors. 7,9,10,17,21,23,39 Okike et al 23 studied the effect of race and ethnicity in patients set to undergo THA in the universally insured healthcare model of Kaiser Permanente. 23 Their study demonstrated that African-Americans and other non-Caucasians have similar or better outcomes than their Caucasian counterparts under this system.…”
Section: Discussionmentioning
confidence: 99%
“…6 Evidence supports the association between THA outcomes and multifactorial patient-level, provider-level and hospital-level racial and socioeconomic disparities. [7][8][9][10][11][12][13][14][15][16] Hospital safety net burden is defined as the proportion of cases at an individual hospital with the primary insurance payer being Medicaid or uninsured; safety net hospitals operate with a mandate or adopted mission to deliver care to patients regardless of their ability to pay. 17 18 Research shows higher rates of mortality, hospitalacquired infection, perioperative complications and poorer markers of surgical quality (timeliness, patient centeredness and equity of treatment) at high safety net burden hospitals.…”
Section: Introductionmentioning
confidence: 99%